Land tax: source of replenishment, and an incentive to improve land use (Journal of Economic Research & Business Administration, 2017)
This article discusses the functioning of the land tax in the tax system of the Republic of Kazakhstan.The mechanism of functioning of the land tax. The analysis of the role of land tax in the tax revenues of thestate budget for 2013-2015 GG Land tax is a direct tax, they are directed to the object of taxation, propertytaxes are taxen- are difficult to hide from the tax. Land tax applies to fixed taxes, and enter fully into thelocal budget revenues. The article deals with some problems in the functioning of the land. Comprehensivestudy of theoretical aspects of functioning of tax on property and approaches to its construction inthe world can help to optimize operating in Kazakhstan, property tax and land tax. Therefore, the researchmethods and techniques of land valuation and determination of the tax base in this area is quite relevant.